2007
DOI: 10.1111/j.1538-7836.2007.02660.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of catheter‐related venous thrombosis with nadroparin in patients receiving chemotherapy for hematologic malignancies: a randomized, placebo‐controlled study

Abstract: To cite this article: Niers TMH, Di Nisio M, Klerk CPW, Baarslag HJ, Bü ller HR, Biemond BJ. Prevention of catheter-related venous thrombosis with nadroparin in patients receiving chemotherapy for hematologic malignancies: a randomized, placebo-controlled study. J Thromb Haemost 2007; 5: 1878-82.Summary. Background: Hemato-oncology patients treated with intensive chemotherapy usually require the placement of a central venous catheter (CVC). CVCs are frequently complicated by catheter-related central venous thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 22 publications
1
46
0
2
Order By: Relevance
“…Although 3 recent randomized, controlled trials demonstrated LMWH and low-dose warfarin to be well tolerated in cancer patients with indwelling catheters, neither approach led to a decrease in catheter-associated thrombosis. [35][36][37] As a retrospective analysis, this study has a number of limitations. First, VTE prophylaxis, in the form of encouraged ambulation, was not standardized or quantified in the medical record.…”
Section: Vte Among Patients Undergoing Hsct 507mentioning
confidence: 99%
“…Although 3 recent randomized, controlled trials demonstrated LMWH and low-dose warfarin to be well tolerated in cancer patients with indwelling catheters, neither approach led to a decrease in catheter-associated thrombosis. [35][36][37] As a retrospective analysis, this study has a number of limitations. First, VTE prophylaxis, in the form of encouraged ambulation, was not standardized or quantified in the medical record.…”
Section: Vte Among Patients Undergoing Hsct 507mentioning
confidence: 99%
“…The incidence of CRT varies considerably among studies, and has dramatically decreased over time. Earlier studies published in the 1980s and 1990s reported rates as high as 66%, but more recent trials have shown that only 14-18% of patients with cancer and a central venous catheter have evidence of CRT when screening venography or ultrasonography is performed [6,[10][11][12]. Symptomatic CRT occurs much less frequently, at a rate of 5% or lower in prospective cohort studies [13][14][15].…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…The efficacy and safety of using anticoagulant prophylaxis to prevent CRT have been investigated in a number of randomized trials (Table 3) [10][11][12][38][39][40][41][42][43][44][45]. The earliest studies suggested that low-dose warfarin (1 mg daily) or LMWH at a standard postoperative prophylaxis dose could significantly reduce the incidence of CRT in cancer patients [38,43].…”
Section: Prevention Of Crtmentioning
confidence: 99%
“…At our institution, we observe guidelines for the management of port-a-caths [21,22]; however, prophylactic low-dose anticoagulation is not used routinely. The use of prophylactic anti-coagulation has been studied extensively in the literature; though two studies demonstrated benefits with mini doses of warfarin, later larger trials showed contradictory results [23][24][25][26]. Similarly, only one study showed better results with the use of low molecular weight heparin (LMWH) in a patient with TIVAP, but subsequent studies were negative [25].…”
Section: Discussionmentioning
confidence: 99%
“…The use of prophylactic anti-coagulation has been studied extensively in the literature; though two studies demonstrated benefits with mini doses of warfarin, later larger trials showed contradictory results [23][24][25][26]. Similarly, only one study showed better results with the use of low molecular weight heparin (LMWH) in a patient with TIVAP, but subsequent studies were negative [25]. Currently, there are no recommendations for the prophylactic use of anticoagulation therapy for patients with a port-a-cath in place.…”
Section: Discussionmentioning
confidence: 99%